THE DIAGNOSTIC VALUE OF PLEURAL BIOPSY IN BRONCHOPULMONARY CARCINOMA. Issue 5 (September 1960) - Pagel, Walter; Goldfarb, Susan
Abstract : The diagnosis of bronchopulmonary carcinoma was either corroborated or arrived at in 13 out of a total of 26 cases by pleural biopsy. Taken as a whole, pleural biopsy is inferior to repeated examination of the pleural exudate for neoplastic cells. In individual observations, however, the former can be found positive at a time when neither the pleural fluid nor any other material provide a diagnostic clue. In an instance of primary pleural growth (mesothelioma) its nature was recognizable in the pleural biopsy material. Pleural biopsy can correctly lead to the diagnostic exclusion of growth in favour of tuberculosis. Pleural biopsy can be suggestive of the rheumatic aetiology of changes. A pleural biopsy positive for carcinoma can be obtained on both sides. All stages, from early submesothelial deposition of individual neoplastic cells to the dense infiltration of the subserous connective and fat tissue, were observed.